Hubungan Antara Dukungan Sosial Dan Kualitas Attachment Pada Ibu Dengan Resiliensi Remaja Quasi Broken Home Di SMP Negeri 3 Babat - Cahyaning Tyas, Alif Dian (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2013)
Abstract, This study aimed to determine the correlation between social support and quality of attachment in mothers with adolescent resilience quasi broken home in SMP Negeri 3 Babat. The subjects were students of SMP Negeri 3 Babat many as 107 people. Sampling using purposive sampling. Data collection instrument used in this study is resilience scale, the scale of social support and quality of attachment scale that refers to making according to Likert scale. Results of data analysis using regression. Anareg get results F = 325.846 with p = 0.00 (p <0,01). Variables of social support and quality of attachment to mother simultaneously and significantly correlated with resilience. Partially, found the value of t Regression between social support with resilience = 10 528, and partial r = 0.718, p = 0.00 (p <0.01), this means that there is a significant positive relationship between social support with resilience. Partial test also found the value of the variable t Regression between attachment quality with resilience = 9.380, and partial r = 0.677, p = 0.000 (p <0.01), this means that there is a significant positive relationship between quality of attachment with resilience. The results showed that the third hypothesis is accepted. Effective contribution of social support variables and quality of attachment towards resilience is at 86.2% (R square =0.862).Â Keywords: Social Support, Quality of Attachment to Mother, Adolescent Resilience Quasi Broken Home in SMP Negeri 3 Babat.